The British system of governmen. - "Birch,Anthony H." (London, 1984)
This edition of this acclaimed text continues to provide a lively, comprehensive and up-to-date account of British political institutions, of the way in which they operate, and of the society in which they developed. It includes new sections on the following key areas: the monarchy and the House of Lords the 1997 general election the transformation of the Labour party and the demise of the Tory's the European Union devolution the judicial system Northern Ireland.
Keywords: Great Britain -Politics and government-1964.